The Challenges of Translating Computer Terminology: Equivalence and Adaptation Issues (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The rapid development of information technology has led to the emergence of numerous specialized terms in English, many of which require precise translation into other languages, including Uzbek. However, achieving equivalence in translation while maintaining the cultural and linguistic integrity of the target language presents significant challenges. This paper explores the difficulties encountered in translating computer terminology from English into Uzbek, examining direct translation and calquing strategies, as well as the impact of globalization on preserving the national identity of technical lexicons. The study highlights the balance between linguistic adaptation and maintaining technical accuracy in translation.